KANDUNGAN MATCHA DALAM TREN GIZI DAN GAYA HIDUP SEHAT GENERASI Z DI ERA DIGITAL: LITERATUR REVIEW - Alya Ananda Nisa; Devvi Mardani; Glory Rezeki Panjaitan; Indah Eka Putri Sihotang; Karina Ajjarah; Syairal Fahmy Dalimunthe (CV. Adiba Aisha Amira, 2025)
In recent years, matcha has gained significant popularity, especially among Generation Z, who are strongly influenced by healthy lifestyle trends and digital information flows. Matcha, a powdered green tea from Japan rich in catechins, dietary fiber, vitamin K, and amino acids such as theanine, is associated with health benefits relevant to the active and nutrition-conscious young generation. Studies indicate that matcha contains higher bioactive compounds than regular green tea and can modulate gut microbiota, support metabolism, enhance cognitive function, and reduce stress. However, excessive consumption may lead to adverse effects like anxiety, insomnia, and impaired iron absorption. Moreover, social media platforms amplify matcha's trendiness among youth by promoting its nutritional value and visual appeal. This study employs a literature review method analyzing scientific articles from the last decade to explore matcha's nutritional content, health benefits, and social media's influence on its consumption trend among Generation Z. The findings suggest matcha’s potential as a functional beverage supporting a healthy lifestyle for Generation Z, influenced by digital era trends in food choices.